An outbreak investigation of typhoid fever in Pondicherry, South India, 2013 - Johnson Cherian; Srinivasan Sampath; Bhuvaneswary Sunderamurthy; Vijay Chavada; Kavita Vasudevan; Anbusenthil Govindasamy (Universiti Kebangsaan Malaysia, 2015)
Background: Preliminary investigation at Pediatric ward of Indira Gandhi Medical College revealed admission of a cluster of typhoid cases who were residents of one particular street in a nearby locality. Objectives: This study was undertaken to estimate the magnitude of the outbreak, identify the source of infection, and, thereby, institute control measures. Materials and Methods: An investigation team including 10 MBBS students carried out a sanitary survey, house-to-house survey, data collection using epidemiological case sheets, and spot mapping. Typhoid diagnosis was confirmed as per the IDSP guidelines, i.e., either a blood culture growth positive for Salmonella typhi or a fourfold rise in antibody titer. An age- and gender-matched case–control study was conducted to find the association of occurrence of typhoid with various possible sources of infection. Water samples were collected from the affected households and public taps for investigation. Results: Rapid survey of all the 6 streets of Thilaspet covered 1106 people living in 283 households. All nine confirmed cases were residents of one particular street. The attack rate calculated was 3.4% in this street. A significant association of occurrence of typhoid was found only with consumption of raw drinking water (OR = 12.6, P = 0.01). Water samples only from the affected street tested positive for the presence of coliforms. The sanitary survey documented water pipeline breakage at the junction of this street. Further spread of disease was stopped by advocating drinking of boiled water and repair of pipeline. Conclusion: Strengthening of disease surveillance for early identification of localized outbreaks and instituting control measures can effectively control disease spread.